Analisis Perbandingan Pembagian Harta Waris berdasarkan Hukum Adat Minangkabau dan KUHPerdata - Musyaffa Abidin, Fikri Rafi; Putri, Andi Sabila; Maryam, Tazkia Asshiva; Maharani, Marsya Arviela; Fahrhezi, Tigor Akhmad; Sakti, Muthia (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract This research compares inheritance practices according to Minangkabau customary law and the Indonesian Civil Code (KUHPerdata) using a normative juridical method. Minangkabau customary law follows a collective system based on the maternal lineage (matrilineal), with an emphasis on preserving wealth within the extended family through collective ownership. In contrast, the Indonesian Civil Code adopts a more individualistic approach, classifying the heirs into four categories and granting inheritance rights based on blood and marriage relations, without gender distinction. This comparison reveals fundamental differences in philosophy, classification, distribution system, and determination of heirs between the two legal frameworks. Despite the differences, both systems strive to provide justice in inheritance distribution according to the cultural and positive law contexts.